Protective role of Nigella sativa in chemotherapy-induced alopecia (Bangladesh Journal of Pharmacology, 2017)
Chemotherapy-induced alopecia affects the pathological as well as the psychological aspects of the cancer patient. In the present study, the protective role of Nigella sativa was evaluated in both adult and newborn albino rats. The anagen phase was first induced. N. sativa oil, N. sativa decoction (5%, 10% and 15%) and minoxidil lotion (standard) were applied daily to the rats two days after the depilation. During the anagen VI phase of the hair follicles, alopecia was induced by giving cyclophosphamide 125 mg/kg, ip to the adult rat and 50 mg/kg to the newborn rats. Cyclophosphamide-induced the alopecia to the whole depilated area of skin in adult rat while alopecia totalis was observed in the newborn rat disease control group. N. sativa oil, N. sativa decoction (5%) showed a significant protective effect against cyclophosphamide-induced alopecia. In conclusion, it is evident that N. sativa provides significant protection against chemotherapy-induced alopecia.Video Clip of Methodology:1 min 43 sec:   Click to watch